Serum leptin, C‐reactive protein, and cancer mortality in the NHANES III - Wulaningsih, Wahyu (John Wiley and Sons Inc., 2015)

(untitled) (Cancer Med)
Adipokines, such as leptin, may affect cancer through its link with inflammation and obesity. We investigated the association between leptin, C‐reactive protein, and risk of cancer death while accounting general and abdominal obesity. From the Third National Health and Examination Survey (NHANES III), we selected 5957 adult men and women with baseline measurements of serum leptin and CRP. Multivariable Cox regression was used to assess leptin and CRP levels (low, moderate, high) in relation to risk of cancer death. Stratification analyses were performed for obesity as defined by body mass index (BMI) and waist circumference. Fine and Gray regression was performed to account for death from cardiovascular disease and other causes as competing events. A total of 385 participants died of cancer during a mean follow‐up of 18 years. After adjusting for BMI and waist circumference, an inverse association with log‐transformed leptin was found for women, with a hazard ratio (HR) of 0.81 (95% confidence interval [CI]: 0.51–1.30) and 0.40 (95% CI: 0.24–0.68) for moderate and high compared to low levels of leptin, respectively; P (trend) = 0.0007). No association for leptin was observed in men, but higher CRP corresponded to increased risk of dying from cancer (HR: 2.98; 95% CI: 1.57–5.64 for the highest vs. lowest categories of CRP). Similar associations were observed with competing risk analysis also adjusted for BMI and waist circumference. Contrasting associations of serum leptin and CRP with cancer mortality may indicate sex‐specific biological or environmental pathways linking obesity and cancer in men and women which warrant mechanistic investigations.